Dental students' and patients' perceived importance and knowledge of dental anxiety - Korpela I; Vaununmaa K; Tolvanen M; Suominen A; Freeman R; Lahti S (WILEY, 2022)
Aim To examine the perceived importance and knowledge of the dental students' in their treatment of dental anxiety according to their year of study and to find out patients' perceived importance of the dental students' knowledge of dental anxiety according to their level on dental fear. Methods Dental students (N = 219) at the University of Turku and non-probability convenience sample of 100 of patients attending the Dental Teaching Clinic were given questionnaires with multiple choice and open-ended questions. Students were categorised into three groups according to the year of study (1-3, 4, 5). Patients were categorised into three groups using the established cut points for Modified Dental Anxiety Scale (no fear = 5-9, low fear = 10-18, high fear = 19-25). The differences between groups were evaluated using cross-tabulations, chi squared and Fisher's exact tests. The open-ended questions were subjected to content analysis. Results Students' perceived importance of dental anxiety did not differ between three groups. Students with greater undergraduate education and clinical experience were more likely to have excellent or quite good knowledge (P < .001). Patients' perceived importance of dental students' knowledge of dental anxiety was greater in patients with high level of fear. The overlapping category that emerged from the open-ended question analysis was communication skills. This appeared to be important for patients with dental anxiety and for dental students in their management of dental anxiety. Conclusion Clinical communication skills should be part of dental anxiety management teaching. Dental students should be able to gain sufficient knowledge and skills in treating dental anxiety before graduating.